FAKTOR RESIKO TERJADINYA ULKUS KAKI DIABETIK PADA PASIEN DIABETES MELLITUS TIPE II: LITERATURE REVIEW - Malik, Muh. Zukri; Sitti Khadija; Mikawati (Journal of Islamic Nursing, 2023)
Type II diabetes continues to increase in prevalence and incidence. One of the important complications of diabetes type II is diabetic foot ulcer, which is a growing public health problem and is a leading cause of amputations and death in diabetic patients. So it is necessary to know what causes diabetic foot ulcers to remain vigilant and prevent this condition. The method used in the preparation of this research is a Literature Review by analyzing several articles that have been determined. This study consisted of ten articles which were analyzed using the manual screening concerning the inclusion and exclusion criteria. The variables studied were neuropathy, duration of diabetes mellitus, foot care, and age. In this study, the results of three articles discussing neuropathy, seven articles discussing the duration of diabetes mellitus, six articles discussing foot care, and four articles discussing age with the occurrence of diabetic foot ulcers. Conclusion: In this study, factors associated with the occurrence of diabetic foot ulcers in patients with type II diabetes were neuropathy, duration of diabetes, foot care, and age.